2016
DOI: 10.1177/0885328216648809
|View full text |Cite
|
Sign up to set email alerts
|

Long-lasting and bioactive hyaluronic acid-hydroxyapatite composite hydrogels for injectable dermal fillers: Physical properties and in vivo durability

Abstract: Hyaluronic acid (HAc)-hydroxyapatite (HAp) composite hydrogels were developed to improve the biostability and bioactivity of HAc for dermal filler applications. Two kinds of HAc-HAp composite fillers were generated: HAcmicroHAp and HAc-nanoHAp composites. HAc-microHAp was fabricated by mixing HAp microspheres with HAc hydrogels, and HAc-nanoHAp was made by in situ precipitation of nano-sized HAp particles in HAc hydrogels. Emphasis was placed on the effect of HAp on the durability and bioactivity of the filler… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
13
0
3

Year Published

2016
2016
2023
2023

Publication Types

Select...
4
1

Relationship

1
4

Authors

Journals

citations
Cited by 32 publications
(25 citation statements)
references
References 47 publications
0
13
0
3
Order By: Relevance
“…6,24,25 In particular, it can be inferred how long wrinkle improvement would maintain according to gel persistence with biostability. 15 According to our previous study, HAc-nanoHAp filler maintained 60% in volume after 4-week injection into nude mouse skin, whereas pure HAc drastically degraded away, retaining only 40%. 15 It is indicated that HAp nanoparticles in HAc-nanoHAp imposed a physical barrier to enzymatic breakdown, which contributing to high resistance.…”
Section: Discussionmentioning
confidence: 84%
See 4 more Smart Citations
“…6,24,25 In particular, it can be inferred how long wrinkle improvement would maintain according to gel persistence with biostability. 15 According to our previous study, HAc-nanoHAp filler maintained 60% in volume after 4-week injection into nude mouse skin, whereas pure HAc drastically degraded away, retaining only 40%. 15 It is indicated that HAp nanoparticles in HAc-nanoHAp imposed a physical barrier to enzymatic breakdown, which contributing to high resistance.…”
Section: Discussionmentioning
confidence: 84%
“…15 According to our previous study, HAc-nanoHAp filler maintained 60% in volume after 4-week injection into nude mouse skin, whereas pure HAc drastically degraded away, retaining only 40%. 15 It is indicated that HAp nanoparticles in HAc-nanoHAp imposed a physical barrier to enzymatic breakdown, which contributing to high resistance. Thus the incorporation of HAp nanoparticles made the gel more durable under physiological condition rather than pure HAc.…”
Section: Discussionmentioning
confidence: 84%
See 3 more Smart Citations